Comparative Studies on the Anticoagulant Profile of Branded Enoxaparin and a New Biosimilar Version. (25th September 2020) - Qneibi, Dalia; Ramacciotti, Eduardo; Macedo, Ariane Scarlatelli; Caffaro, Roberto Augusto; Agati, Leandro Barile; Siddiqui, Fakiha; Kouta, Ahmed; Hoppensteadt, Debra; Fareed, Jawed; Carter, Charles A.
Low molecular weight heparins (LMWH) represent depolymerized heparin prepared by various methods that exhibit differential, biochemical and pharmacological profiles. Enoxaparin is prepared by benzylation followed by alkaline depolymerization of porcine heparin. Upon the expiration of its patent, several biosimilar versions of enoxaparin have become available. Heparinox (Sodic enoxaparine; Cristália Produtos Químicos Farmacêuticos LTDA, Sao Paulo, Brazil) is a new biosimilar form of enoxaparin. We assessed the molecular weight and the biochemical profile of Heparinox and compared its properties to the original branded enoxaparin (Lovenox; Sanofi, Paris, France). Clotting profiles compared included activated clotting time, activated partial thromboplastin time (aPTT), and thrombin time (TT). Anti-protease assays included anti-factor Xa and anti-factor IIa activities. Thrombin generation was measured using a calibrated automated thrombogram and thrombokinetic profile included peak thrombin, lag time and area under the curve. USP potency was determined using commercially available assay kits. Molecular weight profiling was determined using high performance liquid chromatography. We determined that Heparinox and Lovenox were comparable in their molecular weight profile. Th anticoagulant profile of the branded and biosimilar version were also similar in the clot based aPTT and TT. Similarly, the anti-Xa and anti-IIa activities were comparable in the products. No differences were noted in the thrombin generation inhibitory profile of the branded and biosimilar versions of enoxaparin. Our studies suggest that Heparinox is bioequivalent to the original branded enoxaparin based upon in vitro tests however will require further in vivo studies in animal models and humans to determine their clinical bioequivalence.